Perceptions towards female leadership in Malaysia - Mohammad Hassan Hilal , Huda (2014)
Despite a growing number of research focused on the leadership of professional working groups with male leaders, in contrast, research on women leadership has received little attention. This study investigates the perceptions of employees toward women leadership. The study assess the leadership attribute (affection, efficiency or collaboration) that is highly associated with women leadership and to compare the different perceptions between males and females regarding female leadership. Data were collected from 1530 (n = 1530) government, private and semi-government institutions. The results revealed that (1) efficiency was rated as the most common attribute associated with female leadership followed by collaboration and affection, (2) female employees had a significantly higher level of positive perception towards female leadership as compared to male employees and (3) the gender of the immediate superior significantly related to the employees’ positive perception toward female leadership. The implications of the findings for research and practice are discussed.